BUDAYA RELIGIUS: IMPLIKASINYA DALAM MENINGKATKAN KARAKTER KEAGAMAAN SISWA DI MIN KOTA MALANG - Fitriah Rahmawati; Mohammad Afifulloh; Muhammad Sulistiono (Elementeris : Jurnal Ilmiah Pendidikan Dasar Islam, 2020)
This research was conducted to find out how the implementation of cultures that are generally implemented in various elementary schools, especially those in MIN 2 Kota Malang, which is about increasing religious character through the application of religious culture. The research was conducted using observations, interviews and documentation. In this research researchers use interview instruments arranged to get interviews. At this time many children are less concerned about the education of religious characters, the main cause is a poor community environment and the lack of religious character education in every educational institution. In this case researchers will discuss about the religious character of students in MIN 2 Kota Malang , the forms of implementation of religious culture, and the application of religious culture in improving religious character in MIN 2 Kota Malang. Related to this, researchers found its uniqueness in MIN 2 Kota Malang, namely religious character education started early and religious character education is applied through religious cultures that exist in Madrasah.